2008
DOI: 10.1007/s00408-008-9109-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of 18F-FDG PET/CT for Lymph Node Staging in Patients with Operable Non-small-cell Lung Cancer and Inflammatory Lung Disease

Abstract: As 18 F-fluorodeoxyglucose (FDG) is taken up by inflammatory lymph nodes, it could be falsely interpreted as metastasis. Therefore, we evaluated the diagnostic ability of positron emission tomography/computed tomography (PET/CT) for lymph node staging of lung cancer when inflammatory lung disease coexisted. Patients with operable non-small-cell lung cancer and FDG-avid lymph nodes were retrospectively classified into two groups; those with inflammatory lung disease (ILD) and those without it (NILD). Receiver o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
11
1
1
Order By: Relevance
“…FDG-avid silicotic nodule in the right lung was also seen on both scans (arrowheads) NSCLC, with the average sensitivity and specificity of approximately 80 and 90%, respectively [2-5, 10, 20-23]. However, as seen in the present study, the further accumulated experiences showed that non-metastatic, inflammatory LNs showed false-positive FDG uptake on a single scan, especially in a geographic region with patients at high risk of granulomatous or infectious diseases [6][7][8][9][10]. A longterm smoking history induces lymphoid follicular hyperplasia in LNs and also causes false-positive FDG uptake [24].…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…FDG-avid silicotic nodule in the right lung was also seen on both scans (arrowheads) NSCLC, with the average sensitivity and specificity of approximately 80 and 90%, respectively [2-5, 10, 20-23]. However, as seen in the present study, the further accumulated experiences showed that non-metastatic, inflammatory LNs showed false-positive FDG uptake on a single scan, especially in a geographic region with patients at high risk of granulomatous or infectious diseases [6][7][8][9][10]. A longterm smoking history induces lymphoid follicular hyperplasia in LNs and also causes false-positive FDG uptake [24].…”
Section: Discussioncontrasting
confidence: 42%
“…Since Fluorine-18 fluoro-2-deoxy-D-glucose positron emission tomography (FDG PET) is superior to morphologic computed tomography (CT) in the evaluation of LN status in patients with NSCLC, this technique has been increasingly used [2][3][4][5]. Although LN status has been interpreted qualitatively or quantitatively on a single PET scan, based on the general tendency of a higher FDG uptake in metastatic LNs than in non-metastatic LNs [2][3][4][5], the recent studies showed the limitation of this technique due to hypermetabolic LNs associated with pulmonary infectious or granulomatous diseases [6][7][8][9][10][11]. These hypermetabolic benign LNs causing false-positive results coexist in patients with NSCLC and may be a critical problem for management of these patients.…”
Section: Introductionmentioning
confidence: 98%
“…Despite FDG PET/CT scans have shown high sensitivity, specificity, and accuracy for mediastinal LN metastases in NSCLC, still there are a proportion of patients who are inaccurately staged because of the false positives and false negatives. [11][12][13][14] Studies showed that the diagnostic performance FDG PET/CT for mediastinal LN staging in lung cancer was lower in patients with inflammatory lung disease. 13,14 Therefore, we classified our patients into 2 groups based on the presence of pulmonary comorbidity on chest CT or PET/CT images.…”
Section: Discussionmentioning
confidence: 99%
“…1. Data were analyzed based on node [4,18,28,33,34,36,37,[42][43][44], patient [21-24, 29, 30, 35, 38, 39], or both [19, 20, 25-27, 31, 32, 40, 41] in each study. The summary of studies included is presented in Table 1.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%